2015
DOI: 10.1089/jwh.2014.5134
|View full text |Cite
|
Sign up to set email alerts
|

Parity and Risk of Metabolic Syndrome Among Chinese Women

Abstract: Multiparity was associated with increasing risk of metabolic syndrome independent of main covariates in this population of Chinese women. The findings suggested that multiparity may be a risk factor for metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 38 publications
4
31
1
Order By: Relevance
“…This finding is consistent with prior studies among other racial and ethnic groups that observed significant relationships between increasing parity and overall MetS, 12,13,15,16 including statistically significant variations by history of gestational diabetes. 14 Adjustment for BMI attenuated these earlier findings and the associations were no longer statistically significant for some.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with prior studies among other racial and ethnic groups that observed significant relationships between increasing parity and overall MetS, 12,13,15,16 including statistically significant variations by history of gestational diabetes. 14 Adjustment for BMI attenuated these earlier findings and the associations were no longer statistically significant for some.…”
Section: Discussionsupporting
confidence: 92%
“…While our results are similar to those from studies among Chinese and U.S. populations that found a linear association between increasing parity and both higher waist circumference 13 and an increased prevalence of abdominal obesity (waist circumference >88cm), 12 respectively, they are in contrast to studies of Bangladeshi 17 and Iranian 15 women where no association was observed between parity and waist circumference, after adjustment for similar socio-demographic, lifestyle, and reproductive factors. Similarly, a few prior studies also noted a linear association between increasing parity and lower HDL-C 12,13,15 while others found no association. 16,17 In contrast to our findings, most prior studies did not find an association between parity and elevated fasting glucose, 12,13,17 and a few studies observed a linear association between increasing parity and elevated triglycerides.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, a woman’s risk of metabolic syndrome and its components increases with each pregnancy [11, 12]. …”
Section: Introductionmentioning
confidence: 99%